The prevalence and effects of urinary incontinence in women working in the Universitas Academic Hospital, Bloemfontein - Veronique C. Bailey; Meenakshi Bakaya; Siyabulela H. Jada; Kekeletso E. Khalanyane; Wilhelm J. Steinberg; Gina Joubert; Almereau Prollius (African Journal of Primary Health Care & Family Medicine, 2010)
Urinary incontinence affects 30% of women by the time they reach 50 years of age and continues to increase thereafter. Symptoms vary in severity and adversely impact on the physical and psychosocial wellbeing of affected individuals. By means of a self-administered questionnaire, the study investigated the prevalence of urinary incontinence and its effects on the quality of life in women working at the Universitas Academic Hospital in Bloemfontein in 2007. Pregnant women were not included in the study. One hundred and nine questionnaires were analysed. Participants were 24–62 years of age (mean age 44.4 years). Of these, 27.5% reported symptoms of urinary incontinence. Only one affected individual was younger than 30 years. Three-quarters of affected women rated their symptoms as light to moderate. In 34.6% of the affected women, the condition did not interfere with everyday activities at all, but 11.5% reported severe interference. Information regarding urinary incontinence, precautionary measures, such as Kegel exercises, and its associated psychosocial consequences, should be disseminated to women of all ages.